Positron emission tomography assessment of large vessel inflammation in patients with newly diagnosed, biopsy-proven giant cell arteritis: a prospective, case–control study - Prieto-González, Sergio; Depetris, Marina; García-Martínez, Ana; Espígol-Frigolé, Georgina; Tavera-Bahillo, Itziar; Corbera-Bellata, Marc; Planas-Rigol, Ester; Alba, Marco A; Hernández-Rodríguez, José; Grau, Josep M; Lomeña, Franciso; Cid, Maria C (Annals of the rheumatic diseases, 2014)
Background Positron emission tomography (PET) scan is emerging as a promising imaging technique to detect large-vessel inflammation in giant cell arteritis (GCA). However, the lack of a standardised definition of arteritis based on 18fluorodeoxyglucose (FDG) uptake is an important limitation to the use of PET scan for diagnostic purposes. Objective To prospectively assess the intensity and distribution of FDG uptake at different vascular territories in patients with newly diagnosed GCA compared with controls. Methods 32 consecutive, biopsy-proven, GCA patients treated with glucocorticoids for ≤3 days were included. The control group consisted of 20 individuals, who underwent PET/CT for cancer staging. Maximal standardised uptake value (SUVm) was calculated at four aortic segments, supraaortic branches and iliac-femoral territory. Sensitivity and specificity was calculated by receiver–operator characteristic curves (ROC) analysis. Results Mean SUVm was significantly higher in patients than in controls in all vessels explored and correlated with acute-phase reactants and serum IL-6. Mean of the SUVm at all the vascular territories had an area under the curve (AUC) of 0.830, and a cut-off of 1.89 yielded a sensitivity of 80% and a specificity of 79% for GCA diagnosis. There were no significant differences in AUC among the vascular beds examined. Conclusions FDG uptake by large vessels has a substantial sensitivity and specificity for GCA diagnosis.